MODEL ANALISIS ANCAMAN SYN FLOODING DALAM JARINGAN - Andi Andi; Muhammad Siddik Hasibuan (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2018)
Computer security in a network is things that must be considered. Computer in the Network is a system process, from this process there are gaps which the computer can pass, this attack is a DOS type that is SYN Flooding. SYN Flooding works to disable the server by sending a SYN packet in large quantities and such delivery duration fast Security from this attack is by making good firewall and smart system administrator.